Paradigma Literasi Digital dan Implementasi Konsep Smart Digital Untuk Peningkatan Keterampilan Abad 21 - Siswati, Yopi; Kaluge, Laurens; Hariani, Lilik Sri (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This research is motivated by the importance of guiding students in using digital technology in a positive way. The implementation of digital literacy enables students to use digital technology wisely and responsibly. This study aims to explore the importance of digital literacy, the impact of digital technology development on student’s character, the implementation of digital literacy for improving 21st-century skills, and the role of digital literacy for personalizing a generation with strong character, specifically at SMK Budi Mulia Pakisaji. This research is using a qualitative descriptive method, using purposive technique sampling and data triangulation techniques. This study uses an interactive model of data analysis. Data were collected through in-depth interviews, observation, documentation, and open-ended questionnaires. The results show that digital literacy supports the improvement of students’s 21st-century skills, known as the 6Cs: critical thinking, creativity, collaboration, communication, character, and citizenship. Digital literacy is integrated into IPAS (Science, Social, and Environmental Education) learning and implemented through the SMART (Spesific-Measurable-Achievable-Relevant-Time bound) digital concept. The implementation of digital literacy supports the achievement of IPAS learning goals, to make meaningfull learning experience, and students are able to produce a creation in IPAS projects. Students are able to solve problems using digital technology, select useful content, manage their time effectively, and become a lifelong learner. Furthermore, digital literacy supports the students to increase their knowledge, skills, and attitudes aligned with the values of Pancasila.